Self-Adjustment of New Santri Pondok Pesantren in Terms of Self-regulation and Self-acceptance: Penyesuaian Diri Santri Baru Pondok Pesantren Ditinjau dari Regulasi Diri dan Penerimaan Diri - Maula, Atiqo; Affandi, Ghozali Rusyid (Indonesian Journal of Education Methods Development, 2022)
This research is motivated by the existence of a phenomenon that has problems related to the inability to adjust to the new students of the Roudhotul Mutaallimat Islamic Boarding School, Jabon Porong Sidoarjo, which is characterized by these students whining to their parents to go home, not obeying the rules in the Islamic boarding school, even until ran away from the boarding school because the santri did not feel at home in the boarding school, this data was obtained by researchers through interviews and observations in the boarding school environment. This study aims to determine the Self-Adjustment of New Santri Pondok Pesantren Roudhotul Mutaallimat Jabon Porong in terms of self-regulation and self-acceptance. The sample in this study were 79 new students. The sampling technique was carried out by saturated sampling. The data collection in this study used three psychological scales with a Likert scale model, namely the self-adjustment scale, self-regulation scale and self-acceptance scale. Data analysis was carried out using multiple regression correlation statistical test techniques. The results of this study indicate that there is a significant relationship between self-regulation and self-acceptance with adjustment to new students at the Roudhotul Mutaallimat Islamic Boarding School, Jabon Porong, with a correlation coefficient of 0.363 for self-regulation and 0.540 for self-acceptance with each significance of 0.001 > 0.05. The determinant coefficient test also shows a result of 0.300 (R square) which explains that this research variable self-regulation and self-acceptance has an effective effect of 30% on self-adjustment. The test results indicate that the hypothesis can be accepted.